Huge Lateral Rectus Solitary Plasmacytoma Causing Shunt Extrusion - Nikoo Hamzeh; Mona Safizadeh; Zohreh Nozarian; Hiva Saffar; Seyed Mohsen Rafizadeh (Case Reports in Ophthalmological Medicine)
A 54-year-old man with a history of radiotherapy for right maxillary sinus plasmacytoma 3 years previously was referred to an orbital clinic with progressive proptosis in his right eye. His vision had deteriorated after an initial improvement after phacoemulsification 2 years before. He had undergone shunt implantation and later shunt removal following plate extrusion with the diagnosis of neovascular glaucoma following CRVO. His vision remained at no light perception afterwards, despite a controlled IOP with topical medications. In his CT scan, a large orbital mass was seen with lateral rectus involvement. He underwent deep orbitotomy for tumor resection following worsening of symptoms, and his symptoms were improved afterwards. Pathology report was consistent with plasmacytoma with anaplastic features. After tumor resection, he underwent another course of radiotherapy with complete remission of symptoms afterwards.